Optimalisasi Memori Jangka Pendek Anak Usia Sekolah Melalui Intervensi Simultan Dual-Task Training dan Olahraga Aerobik - Zahra Sativani; Resti Meiliana; Abdurrahman Berbudi B.L (jitek, 2026)
Background: Short-term memory disorders can have an impact on a child's future. Purpose: This study aims to determine the effect of a combination of Dual Task Training and Aerobic Exercise on improving short-term memory in 12-year-old children. Method: This research used a quasi-experimental research design with a pre-test and post-test two group design. Carried out for 4 weeks with a frequency of 3 times a week. The research subjects consisted of 28 people, 14 people in the Intervention I group, a combination of Dual Task Training and Aerobic Exercise, and 14 people in the Intervention II Aerobic Exercise group. And measurements were carried out using the Digit Span Test and Harvard Test. Results: Test showed a p < 0.001 in the Combination Intervention of Dual Task Training and Aerobic Exercise, and a p < 0.001 in the Intervention II Aerobic Exercise group. The test of difference of 2 mean is p = 0.01, which means there is a significant difference between the two interventions with the average difference between intervention group I being 2.79 and intervention II being 1.71. Conclusion: This research can be concluded that the combination of Dual Task Training and Aerobic Exercise intervention is more influential in improving the short-term memory of children aged 12 years.